Proyecto ecoturístico como estrategia de conservación de la biodiversidad en fauna y flora de La Reserva Natural de Aves Reinita Cielo Azul y el entorno histórico-cultural. - Bohórquez Ramírez, Saira Yaigné (Universidad Antonio Nariño, 2022)
In this work, the relationship between tourism and the environment is found, where the conservation of natural, historical and cultural resources of the environment is understood .